Specialist Doctors Work Satisfaction Regarding National Health Insurance System : A Case Study Of Regional Public Hospital In Yogyakarta, Indonesia - Riza Mahendra Kusumo (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2021)
Various complaints from hospitals, both at the regional and national levels, stated that they were not satisfied with the rates set by the BPJS. They stated that the rates set were very unrealistic. The purpose of this study was to examine the effect of medical services fee, workload, and assessment work performance on the level of job satisfaction of specialist doctors related to the BPJS service program in Panembahan Senopati District General Hospital, Bantul, D.I Yogyakarta. This study uses quantitative analytical methods which are followed up with qualitative methods. The population of this study is specialist doctors working in Panembahan Senopati Hospital and has functional positions totaling 38 people. Among respondents who were satisfied with respondents who felt dissatisfied had a balanced number, namely as many as 19 people (50%). However, the average value of 78.58 indicates that the average respondent felt dissatisfied. This shows that the majority of specialist doctors in Panembahan Senopati Bantul Regional Hospital are not satisfied with working conditions in Panembahan Senopati Bantul Regional Hospital. There is a significant relationship between medical service variables (X1), workload variables (X2), work performance assessment variables (X3) and job satisfaction specialist doctor Panembahan Senopati Bantul Hospital.